Dynamic Modulation of Keto‐Enol Tautomerism in Electrolytes for Aqueous Zinc Batteries - Song, Li; Yang, Xiaolong; Zheng, Xinhua; Wang, Mingming; Luo, Ruihao; Jiang, Taoli; Zhao, Guili; Shen, Dongyang; Ye, Lyuzhou; Chen, Wei (Angewandte Chemie International Edition, 2025)
The reversibility of zinc (Zn) anode is subject to adverse reactions. Herein we design a dynamic modulation strategy via enol‐keto tautomerism to inhibit the side reactions, thus improving the reversibility of the Zn anode. Density functional theory calculations and experimental results demonstrate the keto form of additives can be adsorbed on the Zn anode, inhibiting dendrite growth, while the enol form can serve as a bidentate ligand to participate in the construction of solvation sheath for Zn2+, enhancing the kinetics of Zn2+ transport, simultaneously suppressing water activity and reducing HER and corrosion. Consequently, the Zn anode with optimal electrolyte additive achieves high reversibility, where Zn||Zn symmetric cells operate over 4000 h at 10 mA cm−2/10 mAh cm−2, and Zn||Cu asymmetric cells have a life for 930 h at 10 mA cm−2/10 mAh cm−2. Further, this dynamic modulation enables Zn||V2O5 full cells to work over 5000 cycles with a capacity retention of 83% at 5 A g−1, and the Zn||Br2 pouch cells deliver a high capacity of ∼180 mAh. This study offers an original perspective on the dynamic regulation of electrolytes for Zn anode. Description: The reversibility of the Zn anode is dramatically improved by dynamic modulation of the keto‐enol tautomerism of β‐dicarbonyl electrolyte additives for suppressing the adverse reactions in this work.